Uveal Effusion Syndrome: Clinical Characteristics, Outcome of Surgical Treatment, and Histopathological Examination of the Sclera - Zhou, Nan; Yang, Lihong; Xu, Xiaolin; Wei, Wenbin (Frontiers in Medicine, 2022)
Purpose: To investigate clinical characteristics and histopathology and to evaluate surgical outcome of quadrantic lamellar-sclerectomy with sclerostomy for uveal effusion syndrome (UES). Design: Retrospective, cohort study Participants: 106 eyes of 66 patients diagnosed with UES treated in Beijing Tongren Hospital from Jan 1, 2001 to June 26, 2021. Methods: Patients were examined by routine ophthalmologic examinations, fluorescein and indocyanine green angiography (FA/ICGA); axial length; Color Diploer Ultrasound (CDU); ultrasound biomicroscopy (UBM), optical coherence tomography (OCT) and optical coherence tomographic angiography (SD/SS-OCTA). Quadrantic lamellar-sclerectomy with sclerostomy was performed at the equator on all patients and histopathologic examination of excised sclera was analyzed on all samples. Main Outcome Measures: Reattachment of the choroid and retina with resolution of the serous fluid, best corrected visual acuity (BCVA), choroidal thickness, and the recurrence of the ciliochoroidal detachment. Results: Two subgroups were identified: In type 1, nanophthalmic eye; the eyeball is small (average axial length 15.83±1.45 mm) with high hypermetropia (average 12.6 diopters); in type 2, non-nanophthalmic eye, the eyeball size is normal (average axial length 23.45±1.68 mm) with or without refractive error, combined with or without systemic symptoms. Histopathologically, types 1 and 2 demonstrated similar abnormal sclera with disorganization of collagen fiber bundles and deposits of proteoglycans in the matrix. Quadrantic lamellar-sclerectomy with sclerostomy was effective for types 1 and 2, inducing postoperative resolution of the subretinal fluid and gained the useful BCVA. The choroidal thickness was significantly different before and after surgery (P<0.05). Approximately 98.1% of cases attain permanent reattachment in 6 months with one operation through this procedure. Single-operation success was 96.2%, and success with one or two operations was 100%. Conclusions: UES is caused by abnormalities of the sclera and increased resistance to transscleral fluid outflow, combining with choroidal thickness. Quadrantic lamellar-sclerectomy with sclerostomy is an effective treatment and can rescue the useful visual acuity.